AUV navigation and guidance in a moving acoustic network - Aníbal Matos (2005)
This paper addresses the navigation and guidance of an AUV operating in a network of moving acoustic beacons. In this network, the vehicle position is obtained from acoustic signals exchanged between the vehicle and the beacons and is computed in a reference frame associated with the moving beacons. The paper describes the operation of the acoustic network, the mission specification and guidance system that computes the references for the vehicle controllers, and the navigation system that produces all the data required by the guidance system.